Beyond Global Food Supply Chains Crisis, Disruption, Regeneration - Stead, Victoria; Hinkson, Melinda (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
"Through a set of incisive essays, this incredibly timely book shows how much the COVID-19 pandemic has exposed both vulnerabilities and opportunities - for (racial) capitalism and its discontents alike to intervene in food supply chains. A most welcome publication!" -Julie Guthman Professor of Social Sciences, University of California, Santa Cruz, USA This open access book takes the upheaval of the global COVID-19 pandemic as a springboard from which to interrogate a larger set of structural, environmental and political fault lines running through the global food system. In a context in which disruptions to the production, distribution, and consumption of food are figured as exceptions to the smooth, just-in-time efficiencies of global supply chains, these essays reveal the global food system as one that is inherently disruptive of human lives and flourishing, and of relationships between people, places, and environments. The pandemic thus represents a particular, acute moment of disruption, offering a lens on a deeper, longer set of systemic processes, and shining new light on transformational possibilities. Victoria Stead is an anthropologist and Australian Research Council DECRA Senior Research Fellow in the Alfred Deakin Institute for Citizenship and Globalisation, Deakin University. Her research sits at the intersection of attention to race and labour relations, land and landscape, and the reverberations of (post)coloniality in Australia and across Australia-Pacific relations. Melinda Hinkson is an associate professor of anthropology at Deakin University and director of the independent Institute of Postcolonial Studies, Melbourne. Her latest research explores creative responses to disruption and visions of agricultural futures in regional Australia. Melinda has published widely on Aboriginal visual production, placemaking, the politics of representation, and the governance of Indigenous difference. .